Trophoblast Differentiation Affects Crucial Nutritive Functions of Placental Membrane Transporters - Karahoda, Rona; Zaugg, Jonas; Fuenzalida, Barbara; Kallol, Sampada; Moser-Haessig, Ruedi; Staud, Frantisek; Albrecht, Christiane (Frontiers in Cell and Developmental Biology, 2022)
Cytotrophoblasts are progenitor cells that proliferate and fuse to form the multinucleated syncytiotrophoblast layer, implicated in placental endocrine and transport functions. While membrane transporters play a critical role in the distribution of nutrients, hormones, and xenobiotics at the maternal-fetal interface, their selectivity to the syncytiotrophoblast layer is poorly characterized. We aimed to evaluate the regulation of placental transporters in response to trophoblast differentiation in vitro. Experiments were carried out in isolated primary human trophoblast cells before and after syncytialization. Gene expression of six molecular markers and thirty membrane transporters was investigated by qPCR analysis. Subsequently, functional expression was evaluated for proteins involved in the transplacental transfer of essential nutrients i.e., cholesterol (ABCA1, ABCG1), glucose (SLC2A1), leucine (SLC3A2, SLC7A5), and iron (transferrin receptor, TfR1). We identified that human chorionic gonadotropin, placental lactogen, endoglin, and cadherin-11 serve as optimal gene markers for the syncytialization process. We showed that trophoblast differentiation was associated with differential gene expression (mostly up-regulation) of several nutrient and drug transporters. Further, we revealed enhanced protein expression and activity of ABCG1, SLC3A2, SLC7A5, and TfR1 in syncytialized cells, with ABCA1 and GLUT1 displaying no change. Taken together, these results indicate that the syncytiotrophoblast has a dominant role in transporting essential nutrients cholesterol, leucine, and iron. Nonetheless, we present evidence that the cytotrophoblast cells may also be linked to transport functions that could be critical for the cell fusion processes. Our findings collectively yield new insights into the cellular functions associated with or altered by the trophoblast fusion. Importantly, defective syncytialization could lead to nutrient transfer imbalance, ultimately compromising fetal development and programming.